Characterization of plasma lactate and core-peripheral temperature gradient in dogs with trauma (Orinoquia, 2022)
In the presence of an injury, patients may present disorders in the tissue perfusion. Failure in tissue perfusion can lead to an irreversible state of shock,if it exceeds the body’s defense mechanisms and is not promptly corrected or therapeutically intervened, increasing the risk of death; This makes itnecessary for the clinician to correctly identify the patient’s condition and to know the pathophysiological changes that occur in critically ill patients inorder to be able to make the therapeutic and case management decisions that are presented in the veterinary clinic. In the Colombian context, affordablemarkers can be found that allow the patient’s prognosis to be established quickly and safely. The aim of this study was to evaluate serum lactate levels and temperature delta as tissue perfusion markers in 43 trauma dogs, which were classified into four groups based on the APACHE VET score,as follows: Group 1 (0 - 10 points), Group 2 (11 - 20 points), Group 3 (21 - 30 points) and Group 4 (≥ 31 points). Serum lactate values of 7.9 ±2.9 mmol / L and core peripheral temperature gradients of 9.0 ± 2.3 degrees Celsius in trauma patients were found to be associated with scoresgreater than 31 points on the APACHE VET score and was a statistically significant difference in contrast to the other groups evaluated. Theseresults allow to conclude that the measurement of serum lactate and the peripheral center temperature gradient could be considered as a marker ofhemodynamic monitoring and prognosis in trauma dogs.